How do patients with Alzheimer's disease imagine their pain?. (7th November 2020) - Borg, Céline; Sala, Emilie; Chainay, Hanna; Labouré, Julien; Getenet, Jean‐Claude; Dorey, Jean‐Michel; Laurent, Bernard; Rouch, Isabelle
Abstract: Introduction: Pain is underdiagnosed and undertreated in patients with Alzheimer's disease (AD). Pain management is of major importance in this population to limit behavioural and functional consequences. Our study aimed to assess the capacity of AD patients to represent pain using a questionnaire exploring daily painful situations and to determine the most appropriate pain scale assessment. Methods: Twenty‐eight patients with mild AD, 21 with moderate AD and 28 matched controls underwent the Situation Pain Questionnaire (SP‐Q) and assessed imaginary pain with four pain scales. Two scores were compared between the three groups: the P(A) discrimination score and the response bias β score. P(A) reflects the degree of discrimination between high‐pain and low‐pain events, whereas the β score means the degree to which situations are considered as painful. Results: Our results showed that AD patients hardly discriminated the high‐ from low‐pain events. Compared to controls, the mean P(A) score was significantly lower for Mild AD ( p < 0.03) and Moderate AD ( p < 0.004). In addition, the β score indicated that the response bias is higher for AD patients ( p < 0.01) in that they overestimated the level of pain. Conclusion: The present results suggest that patients with Mild and Moderate AD are able to recognize and assess an imagined painful situation even though their pain tolerance is lower than that of controls. The pain scales used should be chosen according to the cognitive, sensorial and personal profiles of the patients. Significance: The present research is significant because it examines how patients with Alzheimer's disease understand and assess painful situations. Cognitive impairments can modify this ability. Pain is a sensory and subjective experience and to define its feeling can help us in our clinical practice.